Reversible glomerular damage in disseminated intravascular coagulation. (28th September 2021) - Labbadia, Raffaella; Diomedi Camassei, Francesca; Antonucci, Luca; Guzzo, Isabella; Onetti Muda, Andrea; Spada, Marco; Dello Strologo, Luca
Abstract: Background: Brain death secondary to traumatic brain injury is one of the main sources of organs for transplantation but it can be associated with disseminated intravascular coagulation, which has been considered a relative contraindication for kidney donation. Methods: We describe two successful pediatric cases of kidney transplantation from a single donor with disseminated intravascular coagulation. Results: A 17‐year‐old male donor died from head injury and both kidneys were offered to our center. Within 24 h, donor's Hb and platelets dropped to 8.3 g/dl and 32 000/mcl, respectively, serum creatinine reached 2.01 mg/dl, and urinalysis showed proteinuria (300 mg/dl). Pre‐implant biopsy showed massive occlusion of glomerular capillaries by fibrin thrombi containing fragmented red blood cells and inflammatory cells, and acute tubular damage. Arterioles and small arteries were spared. A diagnosis of DIC was made. The kidneys were transplanted in a 16‐year‐old girl and a 13‐year‐old boy. Slow recovery of graft function was observed in both recipients. On post‐operative day 3, platelets dropped to a minimum value of 66 000 and 86 000/mcl, respectively. Diuresis was always present. On day 4, platelets started to rise. Six months later, both recipients attained normal renal function. A six‐month protocol biopsy showed no microthrombi or other signs of disseminated intravascular coagulation. Conclusions: Despite the limited data available in literature, the outcome of these two cases is positive. Thus, pre‐implant kidney biopsy, even if it reveals massive thrombotic occlusion of glomerular capillaries compatible with diagnosis of disseminated intravascular coagulation, should not be considered an absolute contraindication to transplantation.